DETERMINAN KEPUASAN KONSUMEN DI SUSHI GROOVE KOTA KASABLANKA JAKARTA - Diah Ernawati (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
Consumer satisfaction is an important factor for a company to achieve success. This research aims to determine and analyze the influence of Product Quality, Service Quality, and Brand Image on Customer Satisfaction at Sushi Groove, Kota Kasablaka, Jakarta. Population which is visitors of Sushi Groove Kota Kasablanka Jakarta.The sample consisted of 391 people, taken randomly with convenience sampling method. This study uses multiple linear regression analysis with SPSS Version 22 program. The results of a simple regression analysis is Y = 4.175 + 0.106X1 + 0.111X2 + 0.099X3 + e, which the variables of product quality, service quality, and brand image have a positive and significant effect on customer satisfaction in Sushi Groove Kota Kasablaka Jakarta. Therefore, management of Sushi Groove Kota Kasablaka Jakarta should be able to improve product quality, service quality, and brand image so that customer satisfaction increases and want to make repeat buying.